Theoretical framework and explanatory factors for child-to-parent violence. A scoping review - Arias Rivera, Shirley Jeannet; Hidalgo García, María Victoria (Anales de Psicología / Annals of Psychology, 2020)
Child-to-parent violence is a phenomenon with a fairly high prevalence rate and negative consequences at an individual, family and social level. The aim of this scoping review was to identify the theoretical frameworks and explanatory factors for this phenomenon. The review comprised studies written in English and Spanish since the year 2000, from the following databases: Web of Science, Scopus, PsycINFO, ERIC and Dialnet Plus. A total of 57 relevant studies were identified. The recurrent explanatory factors were: single parenthood, cohesion, stress, family discipline, history of violence, problems at school, clinical disorders and violent peer relationships. The concurrence of school, sibling and dating violence was particularly noteworthy. The theoretical frameworks referred to can be grouped into psychological, communicational, criminological, sociological and broader integrative models (Ecosystemic, Phenomenological and Constructivist). No data was found on interaction patterns, coping strategies or social perceptions of CPV which may influence families immersed in these kinds of situations.